Pengaruh Brand Ambassador, Brand Image, dan Brand Trust Terhadap Repurchase Intention: Studi pada Konsumen Produk Tostos X NCT Dream di Surabaya - Vivia Nur Salsabila Trisnalia; Siti Ning Farida (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study (Consumer Research TosTos x NCT Dream Products on Surabaya) examines the extent to which brand ambassadors, brand image and brand trust affect the intentions of repurchase. This kind of research uses a quantitative approach and an associative strategy. This study's variables were measured using a Likert scale. Participants in the study were all consumers with a minimum age of 17 years who had consumed TosTos X NCT Dream products at least once and lived in Surabaya. Using the Cochran formula, 100 respondents were included in the study. Purposive sampling is the method of sampling that is employed. The data analysis technique in this study uses validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression analysis, and hypothesis testing (F test and T test). The results of the study show that brand ambassador, brand image, and brand trust have a significant positive impact on the repurchase intention. The intention of repurchase is not positively and significantly influenced by the type of brand ambassador. Brand image variable partially has a positive and significant effect on Repurchase intention. Brand trust variable partially has a positive and significant effect on Repurchase intention.